Role of serum ceruloplasmin in the diagnosis of Wilson's disease: A large Chinese study - Yang, Yue; Hao, Wenjie; Wei, Taohua; Tang, LuLu; Qian, Nannan; Yang, Yulong; Xi, Hu; Zhang, Shijie; Yang, Wenming (Frontiers in Neurology, 2022)
Background: Conventionally, serum ceruloplasmin levels below the lower reference limit (0.20 g/L) are considered the diagnostic cutoff for Wilson's disease (WD). However, the lower reference limit varies with different assay methodologies and the individuals in the included studies. The objective of this study was to determine the optimal cutoff value of serum ceruloplasmin for the diagnosis of WD through a large Chinese cohort and to identify factors associated with serum ceruloplasmin. Methods: The cutoff value for ceruloplasmin was developed based on a retrospective derivation cohort of 3548 subjects (1278 WD patients and 2270 controls) and was validated in a separate validation cohort of 313 subjects (203 WD patients and 110 controls). Immunoassay performance was tested by receiver operating characteristic curve (ROC), and differences among the groups were analyzed by the Mann‒Whitney U test and the Kruskal‒Wallis test. Results: The conventional cutoff of serum ceruloplasmin levels of <0.2 g/L had an accuracy of 81.9%, which led to a false-positive rate of 30.5%. The optimal cutoff for the serum ceruloplasmin level for separating WD patients from other participants was 0.13 g/L, as determined by ROC analysis. This cutoff value had the highest AUC value (0.99), a sensitivity of 97.0% and a specificity of 96.1%. Moreover, it prevented unnecessary further investigations and treatments for 492 false-positive patients. By determining the correlation between serum ceruloplasmin and phenotypes/genotypes in WD patients, we found that the serum ceruloplasmin level was lower in early-onset patients and higher in late-onset patients. Interestingly, patients with the R778L/R919G genotype displayed higher serum ceruloplasmin levels than patients with other hotspot mutation combinations. Conclusions: Our work determine the optimal cutoff value of serum ceruloplasmin for the diagnosis of WD and identify differences in serum ceruloplasmin levels with respect to symptom onset age and ATP7B mutations, which may provide some valuable insights into the diagnosis and counsel of patients with WD.